Empathy and the Public Perception of Stillbirth and Memory Sharing: An Australian Case - Keeble, Christina J.; Loi, Natasha M.; Thorsteinsson, Einar B. (Frontiers in Psychology, 2018)
Objective: Stillbirth devastates families and leaves them struggling to grieve the death of their baby in a society that expects grief symptoms to decrease over time. Previous research has suggested that increased memory sharing opportunities can lead to positive mental health outcomes. The aim of the current study was to examine people’s perceptions of stillbirth as well as the perceived appropriateness of affected parents sharing memories of their child. In addition, we examined whether manipulating empathy would have an effect on people’s perceptions of stillbirth. Method: Participants included 200 Australian men and women 18 to 74 years of age (M=36.76, SD=12.59) randomly allocated to one of three experimental conditions (i.e., low empathy, high empathy, and control). The high empathy group watched a video about miscarriage and were instructed to imagine how the people portrayed felt; the low empathy group watched the same video but were instructed to remain detached; and the control group watched an unrelated video. Participants were then asked how much money they would be willing to donate to a fictional stillbirth organisation, followed by the completion of questionnaires measuring (a) perceptions of stillbirth, (b) empathy, and (c) the appropriateness of parents sharing memories of a stillborn child with different groups of people over time. Results: The empathy manipulation had an effect on empathy and the willingness to help effected parents (high empathy vs. control). However, empathy did not have an effect on participants’ perceptions towards stillbirth nor appropriateness of sharing memories. The appropriateness of sharing memories decreased as time passed and social distance increased. Discussion: Individuals who have experienced stillbirth need to be aware that societal expectations and their own expectations in relation to sharing memories may not correspond to each other and that they may need to educate their social group about their need to share memories. Removing the taboo surrounding stillbirth is vital for both parents and those to whom they would wish to communicate.